The detection of antibody to Bacillus anthracis recombinant PA in vaccinated animal serum (Mongolian Journal of Agricultural Sciences, 2020)
Anthrax is a worldwide zoonosis in animals and human. In Mongolia, the confirmed case of anthrax outbreak is reported every year over the past  decade. The prevention and control measure of animal anthrax is vaccination using spore of attenuated Sterne strain, but horse does not get vaccinated in Mongolia. In this study, we constructed the recombinant plasmid for over expression of anthrax protective antigen (PA)/GST fusion protein in pGEX-6P-1 vector and purified the recombinant PA (r-PA) using glutathione Sepharose column under native and denaturing conditions. Since both forms of r-PA were recognized by specific antibody against PA, ELISA system to detect antibody titer in vaccinated bovine serum was constructed. Total of 890 vaccinated cattle serum were collected from 178 cattle at 0, 3, 5, 8 and 12 months’ post vaccination. As negative control, 200 cattle serum from Umnugovi aimag were selected which does not have anthrax foci. All serum was tested by rPA indirect ELISA and, antibody to PA were detected in vaccinated cattle serum but were not detected in negative serum. Therefore, rPA should be used in as monitoring of the anthrax vaccination.